Analysis of labor costs and efficiency of labor resources utilization ("Journal "U". Economy. Management. Finance.", 2025)
In the framework of this study, the author examines the concept and essence of the economic security service. The existing threats in this area have been studied. The methods of evaluating the effectiveness of the economic security service are highlighted. Measures have been developed to improve the activities of the company's economic security service. The prospects of its development are also considered. The practical significance of the work lies in the fact that the results obtained during the research can be applied to solve existing problems.
Keywords: economic security service; efficiency; enterprise; threats; measures; macroeconomics